1986
DOI: 10.1073/pnas.83.24.9348
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of human neuroblastoma DNA polymerase alpha and primase activities by a protein factor isolated from rat liver chromatin.

Abstract: Nuclear protein factor type 1 (NPF-1) thatsimulates IMR-32 primase-associated DNA polymerase a, and a2 activities has been purified from a high-salt extract of liver chromatin from 6-month-old rats. The final purified factor lacks DNA polymerase a, RNA polymerase, and DNA-unwinding or topoisomerase type I activities. The stimulatory activity is destroyed by trypsin (60 min at 37C), DNase II (60 min at 370C), and heat treatment (2 min at 68C). The '2I-labeled NPF-1 does not bind to activated calf thymus DNA or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Pol R has been purified by several eukaryotic sources as a four-subunit enzyme with associated DNA primase activity [reviewed in Wang (1991)], and it has been shown to be absolutely required for initiation of DNA replication both in Vitro and in ViVo (Johnson et al, 1985;Pizzagalli et al, 1988;Challberg & Kelly, 1989;Stillman, 1989). Pol R is likely to be part of a larger multiprotein complex, since several laboratories have isolated pol R as a larger complex containing a number of enzymatic activities such as pol, exonuclease, and ATPase (Hu ¨bscher et al, 1982;Baril et al, 1983;Pritchard & DePamphilis, 1983;Hu ¨bscher & Ottiger, 1984;Takada et al, 1986;Vishwanatha et al, 1986;Ottiger et al, 1987;Biswas & Biswas, 1988). In addition, a 21S enzyme complex has been isolated from HeLa cells which contains pol R, a DNase, DNA ligase, DNA topoisomerase I, RNase H, and PCNA and which is active in the SV40 in Vitro DNA replication system (Malkas et al, 1990).…”
mentioning
confidence: 99%
“…Pol R has been purified by several eukaryotic sources as a four-subunit enzyme with associated DNA primase activity [reviewed in Wang (1991)], and it has been shown to be absolutely required for initiation of DNA replication both in Vitro and in ViVo (Johnson et al, 1985;Pizzagalli et al, 1988;Challberg & Kelly, 1989;Stillman, 1989). Pol R is likely to be part of a larger multiprotein complex, since several laboratories have isolated pol R as a larger complex containing a number of enzymatic activities such as pol, exonuclease, and ATPase (Hu ¨bscher et al, 1982;Baril et al, 1983;Pritchard & DePamphilis, 1983;Hu ¨bscher & Ottiger, 1984;Takada et al, 1986;Vishwanatha et al, 1986;Ottiger et al, 1987;Biswas & Biswas, 1988). In addition, a 21S enzyme complex has been isolated from HeLa cells which contains pol R, a DNase, DNA ligase, DNA topoisomerase I, RNase H, and PCNA and which is active in the SV40 in Vitro DNA replication system (Malkas et al, 1990).…”
mentioning
confidence: 99%
“…These four subunits may likely be a part of a larger multiprotein complex that represents the replicating form of polymerase a. In fact, studies in several laboratories have indicated that DNA polymerase a could be isolated as a large complex accompanied by a number of enzymatic activities such as polymerase, primase, and exonuclease (Hubscher et al, 1982;Baril et al, 1983; Takada et al, 1986;; Biswas & Biswas, 1988). The multimeric form of t This work was supported by a grant from the U.S. Public Health Service.…”
mentioning
confidence: 99%
“…Sequence-specific DNA binding factors are involved in the control of various cellular processes, such as control of gene expression and DNA replication (1)(2)(3)(4)(5)(6)(7)(8)(9). Eukaryotic DNA replication initiates from multiple origins.…”
mentioning
confidence: 99%